Implementation of reliability-centered maintenance (RCM) to improve the availability of CL120 Freightliner tractors in J&J Transportes y Soluciones Integrales Inc. - Yupanqui Apolinario, Eduardo; Rodriguez Carrillo, Sol Angel; Ordoñez Gamarra, Richard Jose (LACCEI, 2024)
The main objective of this work is to implement reliability-centered maintenance (RCM) to improve the availability of the CL 120 Freightliner tractors of J & J Transportes y Soluciones Integrales Inc., assessing the performance from 2020 to 2022. The investigation was carried out in the maintenance area of the company, which is in charge of a fleet of ten tractors. As a first step, the company's situation in the 2019-2020 period was evaluated using maintenance indicators such as MTBF (mean time between failures), MTTR (mean time to respond), availability and critical failures. The information was collected through a documentary analysis. With this baseline, corrective and preventive actions were established. The implementation of the RCM methodology allowed significant improvement in the maintenance management system. Failure Mode and Effects Analysis (FMEA) was implemented in order to identify the critical points of the most frequent failures. With this, the MTBF indicator obtained an increase from 16.81 (year 2019) to 35.16 hours (year 2022), and the MTTR indicator was reduced from 3.91 (year 2019) to 2.69 hours (year 2022). Additionally, the implementation of RCM improves the operational availability of tractors by up to 93%. Finally, it is concluded that the availability of tractor trucks improves significantly with the application of RCM, impacting technically and economically, achieving a higher number of services attended.